Sustainable social spending - Assar Lindbeck (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper discusses a number of threats to the financial sustainability of social spending: increased internationalization of national economies, gradually higher relative costs of producing a number of human services, the ?graying? of the population, slower productivity growth in the private sector, low employment rates, and various types of disincentive effects related to the welfare state itself, including moral hazard. I argue that threats from gradually rising costs of providing human services and disincentive effects of welfare-state arrangements, in particular moral hazard and benefit dependency, are more difficult to deal with than the other threats. I also discuss the choice between ad hoc policy reforms and automatic adjustment mechanisms, delegated to administrative bodies, for dealing with these threats.
Keywords: H53; E62; H31; 330; sustainable fiscal policy; Baumol's disease; moral hazard; automatic adjustment mechanisms; Finanzpolitik; Öffentliche Sozialausgaben; Haushaltskonsolidierung; Moral Hazard